Characterization and Comparative Analysis of Two Rheum Complete Chloroplast Genomes. (22nd June 2020) - Zhao, Kaihui; Li, Lianqiang; Lu, Yazhou; Yang, Junbo; Zhang, Zhirong; Zhao, Fangyu; Quan, Hong; Ma, Xiaojing; Liao, Zhihua; Lan, Xiaozhong
Abstract : Rheum species present a significant economic value. Traditional Chinese medicine rhubarb is an important medicinal material in China. It has a long history of use, with a record of use as early as two thousand years ago. Here, we determined the complete chloroplast genome sequences of Rheum nobile and Rheum acuminatum and comprehensively compared them to two other available Rheum cp genomes at the genome scale. The results revealed cp genomes ranging in size from 159, 051 to 161, 707 bp with a similar typical quadripartite and circular structure. The genome organization, gene numbers, gene order, and GC contents of these four Rheum cp genomes were similar to those of many angiosperm cp genomes. Repeats and microsatellites were detected in the R. nobile and R. acuminatum cp genomes. The Mauve alignment revealed that there were no rearrangements in the cp genomes of the four Rheum species. Thirteen mutational hotspots for genome divergence were identified, which could be utilized as potential markers for phylogenetic studies and the identification of Rheum species. The phylogenetic relationships of the four species showed that the members of Rheum cluster into a single clade, indicating their close relationships. Our study provides valuable information for the taxonomic, phylogenetic, and evolutionary analysis of Rheum .